Correlation between Average Microplastic Abundance and Water Quality Parameters in Sendang Biru Waters, Malang Regency - Ahmad Nuril Fuad Al Fatih; Andi Kurniawan; Maharani Pertiwi Koentjoro (Jurnal Penelitian Pendidikan IPA, 2025)
This research explores the correlation between microplastic abundance and water quality parameters in Sendang Biru Waters, Malang Regency, focusing on two sampling locations: TPI Kondang Buntung and TNI Naval Post. Water samples were collected and analyzed for microplastics using Fourier-transform infrared spectroscopy (FTIR) to identify various polymer types. Statistical methods, including Spearman's correlation and Kruskal-Wallis tests, were employed to assess the relationship between microplastic presence and water quality indicators such as pH, dissolved oxygen (DO), total suspended solids (TSS), and biological oxygen demand (BOD). The results show significant correlations between microplastic abundance and water quality parameters. The correlation coefficient for pH was -0.823 (p < 0.05), indicating an inverse relationship between microplastics and pH. For DO, the correlation coefficient was -0.612 (p < 0.05), suggesting that higher microplastic concentrations are associated with lower oxygen levels. TSS showed a correlation coefficient of 0.711 (p < 0.05), indicating a positive relationship. BOD revealed a coefficient of 0.794 (p < 0.05), suggesting higher microplastic abundance corresponds to greater organic pollution. The study highlights the impact of human activities, especially fishing and tourism, on microplastic pollution and its potential effects on marine ecosystems and human health. Additionally, the presence of microplastics in water bodies raises concerns about their role as carriers of toxic pollutants.